2002
DOI: 10.1073/pnas.192233099
|View full text |Cite
|
Sign up to set email alerts
|

Fast synaptic inhibition promotes synchronized gamma oscillations in hippocampal interneuron networks

Abstract: Networks of GABAergic interneurons are of critical importance for the generation of gamma frequency oscillations in the brain. To examine the underlying synaptic mechanisms, we made paired recordings from ''basket cells'' (BCs) in different subfields of hippocampal slices, using transgenic mice that express enhanced green fluorescent protein (EGFP) under the control of the parvalbumin promoter. Unitary inhibitory postsynaptic currents (IPSCs) showed large amplitude and fast time course with mean amplitudeweigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
555
2
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 497 publications
(594 citation statements)
references
References 45 publications
34
555
2
3
Order By: Relevance
“…These findings showed a deficit in gamma band activity in the MAM-treated rats in both the mPFC and vHipp, the same regions that show significant reductions in PV neuron staining (Lodge et al, 2009). Fastspiking PV interneurons have been shown to be necessary for the generation of gamma band activity (Bartos et al, 2002(Bartos et al, , 2007Buzsáki et al, 1983;Lewis et al, 2011;Whittington et al, 1995), which is also disrupted in schizophrenia (Lewis et al, 2011. Our results showed that stimulation of the BLA induced an inhibition of vHippevoked firing in mPFC neurons at short latencies.…”
Section: Modulatory Influence Of Bla On Vhipp-evoked Firing In Mpfc Isupporting
confidence: 63%
“…These findings showed a deficit in gamma band activity in the MAM-treated rats in both the mPFC and vHipp, the same regions that show significant reductions in PV neuron staining (Lodge et al, 2009). Fastspiking PV interneurons have been shown to be necessary for the generation of gamma band activity (Bartos et al, 2002(Bartos et al, , 2007Buzsáki et al, 1983;Lewis et al, 2011;Whittington et al, 1995), which is also disrupted in schizophrenia (Lewis et al, 2011. Our results showed that stimulation of the BLA induced an inhibition of vHippevoked firing in mPFC neurons at short latencies.…”
Section: Modulatory Influence Of Bla On Vhipp-evoked Firing In Mpfc Isupporting
confidence: 63%
“…Networks of fast-spiking interneurons co-expressing GABA and parvalbumine have been shown to promote synchronization via perisomatic interneuron-interneuron interaction in the hippocampus, in the entorhinal cortex, and in the neocortex (Gulyás et al, 1996;Tamás et al, 1998;Galarreta and Hestrin, 1999;Gibson et al, 1999;Bartos et al, 2002Bartos et al, , 2007Hájos et al, 2004). In addition, non-synaptic interactions through gap junctions may represent an additional mechanism for interneurons synchronization during gamma oscillations (Bartos et al, 2002;Tamás et al, 2000).…”
Section: Role Of Gaba a Receptors In Neuronal Network Oscillationsmentioning
confidence: 99%
“…In addition, non-synaptic interactions through gap junctions may represent an additional mechanism for interneurons synchronization during gamma oscillations (Bartos et al, 2002;Tamás et al, 2000). In vitro studies have also demonstrated that fast oscillations in the gamma range occur spontaneously in isolated cortical networks during up-down states usually associated to both sleep and anesthesia (Sanchez-Vives et al, 2000;Dickson et al, 2003).…”
Section: Role Of Gaba a Receptors In Neuronal Network Oscillationsmentioning
confidence: 99%
“…The IPSPs at basket cellto-basket cell synapses are approximately twice as fast as IPSPs at basket cell-to-pyramidal neuron synapses. The IPSPs rise almost instantly and decay with a time constant of B2 ms. 19,26 As such, rapid inhibition at postsynaptic GABA interneurons is instrumental to the generation of high-frequency oscillations. 18 The excitatory drive to interneurons required to sustain g-frequency oscillations is commonly thought to arise from pyramidal cells 27,28 but evidence for gap junction-mediated excitation across interneurons also exists.…”
Section: Functional Connectivity Is Associated With C-oscillationsmentioning
confidence: 99%